Obraz kobiecości i męskości jako rezultat procesów socjalizacji we współczesnym świecie]. - Ławiak , Alicja (Studia Edukacyjne, 2018)
The main purpose of this paper are gender stereotypes, which determine an image of femininity and masculinity in contemporary culture. The paper considers the consequences of compartmentalization. The author presents her own research about the stereotypes which create an image of femininity and masculinity in contemporary culture. The text concerns the problem of specific developmental limitations, which are hidden behind the aforementioned compartmentalization. The author based her research and theoretical inspiration on social psychology and social pedagogy (interconnected via socialization).